Percutaneous Intervention of Left Main Coronary Artery Chronic Total Occlusion - Murman Kantaria; Vazha Agladze; Pavle Machavariani; Maka Buleishvili; Nino Otarishvili; Ekaterine Sagirashvili; Tamar Sanikidze (Journal of Clinical Case Reports and Images, 2019)
Chronic total occlusion (CTO) of the left main coronary artery (LMCA) is rare on the angiograms; Coronary Artery Bypass Grafting is the standard method of its revascularization. To demonstrate that PCI may in some cases be a safe option for patients with a high-risk surgical category, we report a complex clinical case of revascularization of chronic total occlusion of the LMCA, left anterior descending artery (LAD), and circumflex artery (CX). Methods Recanalization of the occluded LMCA and LAD was performed by utilizing the support-balloon technique, and CTO wires (Miracle 3™ wire, Abbott Vascular; Runthrough® NS Intermediate wire, Terumo); LAD, CX, LMCA, and its bifurcation, were stented with 3 drug-eluting stents (Resolute Integrity DES, Medtronic); the
Keywords: Chronic Total Occlusion